Effect of Tender Coconut Water as Feed Additive on the Cocoon Parameters of Silkworm Bombyx mori - S., Nivetha; A. S., Maheswari; P., Anitha; M.V., Alli (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Impact of feeding tender coconut water to the 5th instar larvae of the multivoltine silkworms along with mulberry leaves seems yielding better results in improving certain aspects of cocoon quality and hence this study was planned to test the efficacy of enhanced feed in the silkworm Bombyx mori through diet which can enhance the economic performance of silkworms, potentially improving silk production. Supplementing the diet of silkworms with tender coconut water had improved their economic performance, leading to increased cocoon weight, pupa weight and shell weight (1.33±0.17 g, 0.92±0.12 g and 0.24±0.34g) when compared to the control group. This suggests that incorporating tender coconut water into the diet of silkworms can enhance their productivity and economic value in Sericulture practices.